The Demographic Profile and Sustainability Growth OF The Bidayuh Population of Sarawak - Lam, Chee Kheung; Shahren Ahmad, Zaidi Adruce (Human Resource Management Academic Research Society (HRMARS), 2018)
Bidayuh is one of the seven major ethnic communities in Sarawak Malaysia, whose population number ranks fourth among all the communities. The analysis and description of the quantity and quality of Bidayuh population give a clear pattern and trends of change of Bidayuh population for the last 60 years, from 1947 to 2010. The study shows that the number of Bidayuh has increased almost 5 times since 1947. This is demonstrated by the annual growth rate and the percentage increase of the Bidayuh population over these years. It is evidenced from the analysis that the Bidayuh population has experienced a slower annual growth in recent years; this pattern simultaneously reflects the positive improvement of the social and economic conditions of the community. Although the growth rate of the Bidayuh has fallen, its size will still grow in absolute number, and the total Bidayuh could reach 220,000 in 2020. In view of the decline of the Bidayuh population which is slower than the Iban, the Melanau, the Chinese, and the Others, the proportion and growth of Bidayuh population in Sarawak population is therefore still sustainable.